Kurikulum Pendidikan Ilmu Komunikasi dan Tantangan Teknologi Informasi - Hafied Cangara (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
The Communication Education Curriculum and The Challenges of Informational Technology. Communication education has recently attracted high school graduates in Indonesia. There is a challenge of how communication education fulfills their needs and the employment market in general. Based on the case, this article suggests modification of communication curriculum to adjust educational system since Indonesia adopt two higher education levels, undergraduate and graduate. The curriculum of undergraduate focuses on practical and basic courses, while the graduate focuses on theory, philosophy and problem analysis. On relationship with the curriculum modification, the communication education institution must provide communication laboratory to support teaching and learning process suited to the development of information technology.